A rare case of isolated paediatric central nervous system melioidosis: an imaging chameleon - Mohamed, Nurdiyana; Yahya, Muhammad Zakwan; Abdul Samat, Muttaqillah Najihan; Abdul Hamid, Hamzaini (RSIS International, 2024)
Burkholderia pseudomallei, the agent of melioidosis, can cause multisystemic infections, including rare cases in the central nervous system (CNS). Isolated CNS melioidosis is particularly rare, with a 3% of cases in long-term study. In this region that is high endemicity, risk factors include direct contact with contaminated soil or water, particularly among individual with immunosuppressive condition. Without timely intervention, CNS melioidosis will lead to high mortality and morbidity rate. Case Presentation: A 6-year-old boy with G6PD deficiency and acute lymphoblastic leukaemia (B cell ALL) presented with a persistent headache and intermittent fever for two months and vomiting for one day. CNS examination was unremarkable. CT and MRI revealed a right fronto-parietal rim-enhancing lesion with mass effect, suggesting meningeal tuberculoma, infection, or malignancy. Abdominal ultrasound and chest x-ray were negative for abscesses. Craniotomy and tumour excision were performed, and culture confirmed Burkholderia pseudomallei. Conclusion: Imaging is essential for differentiating CNS melioidosis from malignancy and characterizing the infection. Diffusion-weighted imaging (DWI) on MRI can help distinguish pyogenic abscesses from cystic tumours. The involvement of white matter tracts and brainstem in CNS melioidosis aids differentiation from other infections, like tuberculosis. In endemic regions, CNS melioidosis should be considered in patients with relevant risk factors, clinical suspicion, and radiological evidence. Microbiological diagnosis is vital for early targeted therapy and improved recovery.